Early gallbladder carcinoma with cholelithiasis: a rare case report - A. C., Senthil Kumar; S., Balamurali; S., Reshma (International Surgery Journal, 2017)
Gall bladder carcinoma is an exceedingly rare and fatal cancer with a high mortality rate. Detecting gall bladder carcinoma in early stages can be difficult, despite improvements in ultrasound and computed tomography (CT) imaging. Most diagnoses of gallbladder carcinoma are made at advanced stages, with majority being found incidentally during surgery for cholelithiasis. The presented case demonstrates suspicion of Gallbladder carcinoma pre-operatively.